2019
DOI: 10.25170/ijelt.v14i2.1443
|View full text |Cite
|
Sign up to set email alerts
|

The use of video-based reflection to facilitate pre-service English teachers’ self-reflection

Abstract: As self-reflection is crucial for improving the professional identity of pre-service teachers, it is paramount to discover ways that may assist them to reflect more effectively. This study investigates how self-reflection may be enhanced by the use of video recording as compared to that which is facilitated only by students’ memories. Employing a descriptive qualitative analysis method, the research uses reflection journals and interviews from pre-service English teachers of two available microteaching classes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 13 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…Video-based reflection has generally been studied with a focus on using video recordings for selfreflection in teacher education including language teachers (Brouwer, 2015;Cavanagh, Bower, Moloney & Sweller, 2014;Setyaningrahayu, Widhi & Murtisari, 2019). Schwartz, Lin and Holmes (2003) point out the importance of using technology for facilitating reflection and minimising cultural distance by claiming that "technology enables manageable cross-cultural exchanges that target specific learning goals for reflection" (p. 302).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Video-based reflection has generally been studied with a focus on using video recordings for selfreflection in teacher education including language teachers (Brouwer, 2015;Cavanagh, Bower, Moloney & Sweller, 2014;Setyaningrahayu, Widhi & Murtisari, 2019). Schwartz, Lin and Holmes (2003) point out the importance of using technology for facilitating reflection and minimising cultural distance by claiming that "technology enables manageable cross-cultural exchanges that target specific learning goals for reflection" (p. 302).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They stated that this assignment helped them to develop a clearer sense of how to behave like a teacher and see classroom situations from the perspective of a teacher rather than student which gave them more confidence in their teaching (Koc 2011 ). Another study praised video recording of micro teaching because it was found to focus pre-service EFL teachers’ attention more upon teaching-related and actionable concerns like classroom management and self-management rather than their more subjective feelings about the experience which ultimately had minimal impact on their classroom practice (Setyaningrahayu et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, video provides an audio-visual record of a teaching situation (Quigley and Nyquist 1992 ). It can focus a learner’s attention and help them to better understand the events it contains by giving them the ability to pause, rewind and replay to review, annotate and analyze it in considerable detail (Hung et al 2004 ; Setyaningrahayu et al 2019 ; Snoeyink 2010 ). This enables review of the teaching and the ability to notice aspects of it that would ordinarily be overlooked (Zhang et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations